Peran Return on Asset dalam Memoderasi Hubungan Biaya Operasional Pendapatan Operasional, BI Rate, dan Capital Adequacy Ratio Terhadap Persentase Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah di Indonesia - wahyuputri; Rahman, Taufikur (Journal Of Islamic Economics And Finance, 2022)
This study aims to determine the role of Return on Assets (ROA) in moderating the relationship between Operating Costs and Operating Income (BOPO), BI Rate, and Capital Adequacy Ratio (CAR) to the percentage of profit sharing on mudharabah deposits at Islamic Commercial Banks in Indonesia. This study uses quantitative approach to Islamic commercial banks registered at Financial Services Authority as the population. The data analysis in this study used multiple linear regression with Moderated Regression Analysis (MRA) test. The results showed that the BOPO and BI Rate had no significant effect on the percentage of profit sharing for mudharabah deposits. CAR shows that this variable has a negative and significant effect on the percentage of profit sharing for mudharabah deposits. Based on the MRA test, the results show that ROA can moderate the relationship between BOPO variable and the percentage of profit sharing for mudharabah deposits. Meanwhile, ROA cannot moderate the relationship between BI Rate variable and the CAR variable on the percentage of profit sharing for mudharabah deposits at Islamic Commercial Banks in Indonesia.